Práticas sociais e identidades profissionais de mulheres engenheiras: problematizando gênero e resistência feminina nas relações de trabalho - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Gender studies are important to stimulate and expand female insertion in all fields of science, as well as to reflect on the women trajectory and their position in the world of work, especially in professions considered to be male, such as civil, electrical, software and agronomy engineering. In this sense, the main objective is investigate how four women face the profession challenges, observing whether they experience gender discrimination in their daily lives, in professional life or in private life as a result of their profession, for understand how is the construction process of professional identity from the experiences reported. The research adopts a qualitative approach, aligned with the theoretical principles of Critical Applied Linguistics (CAL) and Feminist Theory, considering their study possibilities based on the language aspects. Therefore, to answer the research question and achieve the proposed objectives, I use as tools for generating empirical material the conversation circle (CC), individual interviews, written narratives and notes in a field diary, to bring to the surface the critical moments experienced by the engineers, under the interpretative aegis of analysis. The results indicate that social and cultural factors interfered in their professional choices and academic trajectories, such as: family, college and media. What prevented/prevented professional improve is gender inequality and sexism. I also reinforce that this work contribution is to "promote voice" to these women, to allow us to "listen" to the representations they make of the reality of the Engineering field, aiming at co-construction and reframing of this experience, for reduce gender inequalities.
Social practices and professional identities of women engineers: problematizing gender and female resistance in relations of job
Keywords: Mulheres - Profissão - Desigualdade de gênero; Mulheres - Linguagem - Vida profissional; Mulheres - Práticas sociais - Discriminação; Mulheres - Profissão de Engenharia - Identidades e discriminação; Women - Profession - Gender inequality; Women - Language - Professional life; Women - Social practices - Discrimination; Women - Engineering Profession - Identities and Discrimination; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::EDUCACAO